Laser-vacuum deposited ITO thin films for optoelectronic applications - Toikka, Andrei; Kamanina, Natalia (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In the current paper, it has been considered the relief features and electric properties of the transparent contacts based on the indium tin oxides. During the formation of samples, the laser oriented deposition method using the CO2 laser operated at the wavelength of 10.6 um and with the power of 30 W has been used. The deposition process has been revealed via varied the intensity of external electric field in the range of 100-600 V/cm. The influence of the electric field on the deposition process and its correlation with the relief features and electric properties have been evaluated.